Pembelajaran Matematika Melalui Metode Bermain - Erawaty, Nur; Thoha, Syamsuddin; B., Hasmawati; Kasbawati, Kasbawati; Aris, Naimah; Sirajang, Nasrah; Sahriman, Sitti; Anwar, Andi M.; Aidawayati, Aidawayati; Jusmawati, Jusmawati; Saputra, Edy (Dewan Pimpinan Daerah (DPD) Forum Dosen Indonesia JATIM, 2019)
The achievement of Mathematics contestants from the City of Makassar is very concerning. In March 2018 elementary school mathematics competition was held. Of the 186 participants from Makassar, there were only 56 students who got scores above zero. Only about 30%. Other students get zero or less than zero (negative). There was a decrease in interest and achievement in Mathematics in elementary school students in Makassar. The solution offered was training for Mathematics Elementary School teachers by emphasizing learning method with playing. This is intended so that children have enjoyed Mathematics from the beginning so that in the future the interest in learning Mathematics will be even greater.